Treatment of Resistant and Refractory Hypertension - Acelajado, Maria Czarina (Circ Res, 2019)
Resistant hypertension is defined as uncontrolled blood pressure despite the use of 3 or more antihypertensive agents of different classes, including a diuretic, usually thiazide-like, a long-acting calcium channel blocker, and a blocker of the renin- angiotensin system, either an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker, at maximal or maximally tolerated doses. Antihypertensive medication non-adherence and the white coat effect, defined as elevated blood pressure when measured in clinic but controlled when measured outside of clinic, must be excluded to make the diagnosis. Resistant hypertension is a high risk phenotype, leading to increased all-cause mortality and cardiovascular disease (CVD) outcomes. Healthy lifestyle habits are associated with reduced CV risk in patients with resistant hypertension. Aldosterone excess is common in patients with resistant hypertension, and addition of spironolactone or amiloride to the standard 3-drug antihypertensive regimen is effective at getting the blood pressure to goal in most of these patients. Refractory hypertension is defined as uncontrolled blood pressure despite use of 5 or more antihypertensive agents of different classes, including a long acting thiazide-like diuretic and a mineralocorticoid receptor antagonist, at maximal or maximally tolerated doses. Fluid retention, mediated largely by aldosterone excess, is the predominant mechanism underlying resistant hypertension, while patients with refractory hypertension typically exhibit increased sympathetic nervous system activity.